Aiming strategy affects performance-related factors in biathlon standing shooting - Köykkä, M.; Ihalainen, S.; Linnamo, V.; Ruotsalainen, K.; Häkkinen, K.; Laaksonen, M. S. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study focused on investigating differences in shooting performance and performance-related factors between two different aiming strategies (HOLD, low radial velocity during the approach 0.4-0.2 seconds before triggering, and TIMING, high radial velocity) in biathlon standing shooting. A total of 23 biathletes fired 8 × 5 standing shots at rest (REST) and 2 × 5 shots during a race simulation (RACE). Shooting performance (hit point distance from the center of the target), aiming point trajectory and postural balance were measured from each shot. Shooting performance was similar both at REST (HOLD 33 ± 5 mm vs TIMING 38 ± 8 mm, P = .111) and in RACE (40 ± 11 mm vs 47 ± 12 mm, P = .194). Better shooting performance was related to smaller distance of the aiming point mean location (REST r = 0.93, P < .001, RACE r = 0.72, P = .018) and higher time spent within 2/3 of the distance of the hit area edge from the center 0.6-0.0 seconds before triggering (REST r=-0.88, P = .001, RACE r=-0.73, P = .016) in HOLD, and to lower aiming point total velocity 0.6-0.0 seconds before triggering (REST r = 0.77, P = .009, RACE r = 0.88, P = .001) and less aiming point movement 0.2-0.0 seconds before triggering (REST r = 0.82, P = .003, RACE r = 0.72, P = .012) in TIMING. Postural balance was related to shooting performance at REST in both groups and in RACE in TIMING. Biathletes using the hold strategy should focus on stabilizing the aiming point before triggering and aiming at the center, whereas biathletes using the timing strategy benefit of decreasing the total velocity during the final approach as well as minimizing the aiming point movement right before triggering.